Highly luminescent Gd2O2S:Er3+,Yb3+ upconversion microcrystals obtained by a time- and energy-saving microwave-assisted solid-state synthesis - Machado Ian P; de Wit Jur; van Bunningen Arnoldus J; Pedroso Cássio CS; Rodrigues Lucas CV; Brito Hermi F; Meijerink Andries (ELSEVIER SCIENCE SA, 2025)
Er3+-doped and Er3+,Yb3+-co-doped Gd2O2S are one of the most efficient upconversion (UC) materials available to date. However, preparing lanthanide oxysulfides can be challenging as it requires several hours of heating at > 1000 degrees C in high power furnaces. Nonetheless, in designing a new synthesis technology for UC materials, one should consider that these systems suffer from defect quenching, responsible for significant optical energy losses. In this work, the microwave-assisted solid-state (MASS) synthesis was explored as an alternative to synthesize this class of materials, using two different starting compounds - lanthanide oxides (Ln2O3) and hydroxycarbonates (Ln(OH)CO3), where Ln3+: Gd, Er, Yb. Different Er3+,Yb3+ concentrations were investigated, and the Er3+(5%),Yb3+(5%) and Er3+ (1%),Yb3+ (10%) were shown to give the most intense UC output comparable to commercially available materials. Using Ln(OH)CO3 instead of the more common Ln2O3 for the MASS synthesis contributed to higher UC efficiencies and a more homogeneous Er3+ and especially Yb3+ distribution through the Gd2O2S lattice as verified by luminescence lifetime measurements. These high-quality materials were prepared in a simple two-step synthesis of 50 min and using a domestic microwave oven, leading to a remarkable decrease of 79% in processing time and 93% in energy consumption, making the MASS method suitable to be explored as an alternative synthesis methodology for high performance UC materials.
(c) 2023 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).